Les lois linguistiques de la brièveté : conformité chez le lémurien chanteur Indri indri - Daria Valente; Chiara De Gregorio; Livio Favaro; Olivier Friard; Longondraza Miaretsoa; Teresa Raimondi; Jonah Ratsimbazafy; Valeria Torti; Anna Zanoli; Cristina Giacoma; Marco Gamba (Revue de Primatologie)
Vocal and gestural sequences of many primate species conform to two principles of compression: the compensation between the length of a construct and that of its constituents (Menzerath-Altmann law) and an inverse relationship between signal length and occurrence (Zipf's law of abbreviation). Although Zipf's law is considered a universal in animal communicative systems, evidence for the adherence of non-human primate vocal behavior to linguistic laws is debated, and information on strepsirrhines is absent. We investigated the vocal behavior of the only singing lemur (Indri indri) to test whether the song of this species shows indication for compression. Because roars have a chaotic structure that prevents the recognition of each individual emission, and long notes are mainly emitted by males, we relied on the core part of the song (i.e., descending phrases, composed of two to six units). Our results indicate that songs conform to both laws. Indeed, shorter phrases are more likely included in the songs, in conformity to Zipf’s law, and unit length decreases with increasing phrase size, in line with Menzerath-Altmann law. Furthermore, despite a sexual dimorphism of both units and phrases duration, these laws characterize the vocal sequences of both sexes. In conclusion, we provide the first evidence for a compromise between signal duration and occurrence in the vocal system of a strepsirrhine species, suggesting that, in primates, selective pressures for compression are more ancestral than previously assumed.